DETERMINAN PENGUNGKAPAN SHARIA COMPLIANCE PERBANKAN SYARIAH BERDASARKAN STANDAR AKUNTANSI SYARIAH INTERNASIONAL AAOIFI - Nur Azifah; Khairul Fitroh (Jurnal Akuntansi dan Manajemen Bisnis, 2022)
This study aims to determine the factors that influence sharia compliance based on International Sharia Accounting Standards (AAOIFI) in Islamic banking in Indonesia. This study uses secondary data from the annual report of Islamic banking for the 2016-2020 period. This study aims to analyze the shariah board tenure, shariah board educational background, firm size, and firm age on shariah compliance disclosure in sharia banking. The method used is panel regression analysis. Based on the test results, the variables of board tenure, DPS education, and firm age do not have a significant influence due to the lack of diversity in the tenure of the board and DPS educational background, and the older firm age does not guarantee the fulfillment of sharia compliance which refers to AAOIFI. Meanwhile, the effect of board age and firm size indicates that the age diversity of the board, which is dominated by older age will have more experience and competence, as well as an increase in the size of the banking system, which has the potential to increase the disclosure of sharia compliance according to AAOIFI standards.